A Case Report on Drug-Induced Hepatic Failure in a Young Child Infected with HAV (Bangladesh Journal of Medical Microbiology, 2023)
Hepatitis A virus (HAV) is typical enterovirus that may cause liver damage. This infection may vary in intensity from a few weeks of moderate sickness to many months of severe illness. It may sometimes lead to liver failure and death, especially in individuals with a preexisting health condition or a compromised immune system. Hepatitis A infection is most common in children in developing countries. A very tiny percentage of those who have hepatitis A may die from fulminant hepatitis or extrahepatic manifestations. One of the main causes of liver damage is an adverse drug reaction, which may require withdrawing the offending medication, being hospitalized, or even undergoing liver transplantation. The most frequent cause of acute liver failure is, in fact, drug-induced hepatotoxicity. Acetaminophen is usually used in mild analgesic or antipyretic with in-dose limitations. Use of Acetaminophen during a prodromal period of Hepatitis A may induce acute liver failure from which mild ascites and pleural effusion may develop. There have been isolated cases of these pediatric Hepatitis A symptoms occurring in isolation, but it is highly unusual for them to coexist. In this article, a young boy with Hepatitis A infection is described who had both of these pleural effusions and ascites at the same time. Hepatitis A in children with drug-induced consequences such as liver failure is carefully treated. First-care clinicians must be aware of paracetamol-induced juvenile hepatitis extrahepatic symptoms. This article recommends before fever therapy cause of fever should be excluded.Bangladesh Journal of Medical Microbiology, July 2022;16(2):72-75